Manajemen Kepala Sekolah dalam Melaksanakan Perencanaan, Implementasi, Penilaian dan Tindak Lanjut Supervisi Akademik - Muklis Riyanto; Rambat Nur Sasongko; Muhammad Kristiawan; Edy Susanto; Desi Tri Anggereni (Alignment:Journal of Administration and Educational Management, 2021)
The purpose of this study was to describe the management of the principal in carrying out planning, implementation, assessment and follow-up of academic supervision at SMA Negeri 6 Lubuklinggau. Data collection techniques include observation, interviews and documentation studies. Data analysis techniques include data collection, data reduction, data presentation and summarizing. Research result; 1) planning for academic supervision has been carried out in accordance with procedures, 2) implementation of academic supervision including methods, media, and classroom management has been carried out properly, 3) assessment of academic supervision includes techniques and procedures that have been carried out with good coaching, 4) follow-up academic supervision including planning, implementation, and assessment, good guidance has been carried out by the school principal. In conclusion, the management of the principal in carrying out academic supervision has gone well in accordance with existing procedures, but in planning and assessing the principal should be able to maintain and even make innovations in conducting academic supervision. Keywords: Management, Planning, Implementation, Assessment, Follow-up Supervision